Detection of Pesticide Residues in Food Using Surface-Enhanced Raman Spectroscopy: A Review - Xu, Meng-Lei; Gao, Yu; Han, Xiao Xia; Zhao, Bing (Journal of agricultural and food chemistry, 2017)
Pesticides directly pollute the environment and contaminate foods ultimately being absorbed by the human body. Their residues contain highly toxic substances that have been found to cause serious problems to human health even at very low concentrations. The gold standard method, gas/liquid chromatography combined with mass spectroscopy, has been widely used for the detection of pesticide residues. However, these methods have some drawbacks such as complicated pretreatment and cleanup steps. Recent technological advancements of surface-enhanced Raman spectroscopy (SERS) have promoted the creation of alternative detection techniques. SERS is a useful detection tool with ultrasensitivity and simpler protocols. Present SERS-based pesticide residue detection often uses standard solutions of target analytes in conjunction with theoretical Raman spectra calculated by density functional theory (DFT) and actual Raman spectra detected by SERS. SERS is quite a promising technique for the direct detection of pesticides at trace levels in liquid samples or on the surface of solid samples following simple extraction to increase the concentration of analytes. In this review, we highlight recent studies on SERS-based pesticide detection, including SERS for pesticide standard solution detection and for pesticides in/on food samples. Moreover, in-depth analysis of pesticide chemical structures, structural alteration during food processing, interaction with SERS substrates, and selection of SERS-active substrates is involved.